2014
DOI: 10.1016/j.yexcr.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Altered epigenetic regulation of homeobox genes in human oral squamous cell carcinoma cells

Abstract: To gain insight into oral squamous cell carcinogenesis, we performed deep sequencing (RNAseq) of non-tumorigenic human OKF6-TERT1R and tumorigenic SCC-9 cells. Numerous homeobox genes are differentially expressed between OKF6-TERT1R and SCC-9 cells. Data from Oncomine, a cancer microarray database, also show that homeobox (HOX) genes are dysregulated in oral SCC patients. The activity of Polycomb repressive complexes (PRC), which causes epigenetic modifications, and retinoic acid (RA) signaling can control HOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…Further, Chromatin immunoprecipitation (ChIP) studies for H3K9me3 in keratinocyte cell line (OKF6-TERTIR) and tongue carcinoma cell line (SCC-9) corroborated differential expression in the normal and cancer cell lines. Besides, the downstream processes were associated with HOX genes (HOXB7, HOXC10, HOXC13 and HOXD8) in the cancer cell line and IRX1 and IRX4 genes in the keratinocytes [101,102]. The presence of Histone 2 variant c-H2A.X was reported in 30% oral cancer tissue (n = 42), and 61% oral dysplastic tissue (n = 34) [103].…”
Section: Histone Modifications In Oral Cancermentioning
confidence: 98%
“…Further, Chromatin immunoprecipitation (ChIP) studies for H3K9me3 in keratinocyte cell line (OKF6-TERTIR) and tongue carcinoma cell line (SCC-9) corroborated differential expression in the normal and cancer cell lines. Besides, the downstream processes were associated with HOX genes (HOXB7, HOXC10, HOXC13 and HOXD8) in the cancer cell line and IRX1 and IRX4 genes in the keratinocytes [101,102]. The presence of Histone 2 variant c-H2A.X was reported in 30% oral cancer tissue (n = 42), and 61% oral dysplastic tissue (n = 34) [103].…”
Section: Histone Modifications In Oral Cancermentioning
confidence: 98%
“…The mechanism of this widespread dysregulation of HOX genes in HNSCC has not been clearly established. The alterations in promoter methylation and histone modifications mentioned earlier play a role , as do changes in microRNA expression, such as miR‐196 , and other transcription factors, such as POU2F1 . There are numerous reports of more widespread effects of alterations in the expression of miRNAs and lincRNAs encoded within the HOX gene cluster.…”
Section: Hoxd Clustermentioning
confidence: 97%
“…SUZ12 depletion by shRNA technology increased HOXB7, HOXC10, HOXC13, and HOXD8 transcript levels in OKF6‐TERT1R cells, suggesting that the silencing of these HOX genes in non‐tumorigenic, oral keratinocytes results from the deposition of the H3K27me3 mark by EZH2, a component of PRC2 complex. In contrast, SUZ 12 depletion did not increase the transcript levels of the homeobox genes IRX1, IRX4, SIX2, and TSHZ3 in tumorigenic SCC‐9 cells (Marcinkiewicz and Gudas, ).…”
mentioning
confidence: 98%
“…We recently discovered a role for the epigenetic mark H3K27me3 in the regulation of homeobox gene transcript levels in human oral keratinocytes and tongue squamous cell carcinoma (SCC) cells (Marcinkiewicz and Gudas, ). We found that the levels of the H3K27me3 marks at chromatin near homeobox genes were inversely correlated with the transcript levels in non‐tumorigenic, immortalized human oral keratinocytes (OKF6‐TERT1R) and tumorigenic oral SCC‐9 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation